The Influence of Marketing Communications on Customer Loyalty At PT. Citra Van Titipan Kilat (TIKI) Cabang Sumedang - Sutisna, Nana; Yuniawati, Ayi Srie; Ginanjar, Yayat (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
Marketing communication can be an effective form of communication channel to handle consumer complaints effectively and efficiently. By paying attention to the importance of marketing communication, companies can design more effective communication strategies to achieve their marketing goals, and can build strong customer loyalty. In this study, the method used is the quantitative method. According to Priyono (Sahir, 2021:13)